Hubungan Tingkat Pengetahuan dan Kesadaran Penggunaan Tabir Surya pada Trainer Peselancar di Pantai Kuta Bali Tahun 2025 - Valenia Elungan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
High exposure to sunlight in tropical areas such as Indonesia increases the risk of skin damage due to ultraviolet (UV) radiation. Sunscreen functions to protect the skin from the bad effects of UV rays, and a good level of knowledge is expected to increase awareness of its use. Surf trainers, who are frequently exposed to sunlight, need proper knowledge and awareness to prevent these negative impacts. This research aims to determine the relationship between the level of knowledge and awareness of the use of sunscreen among surfing trainers at Kuta Beach. The research used an observational design with a cross-sectional approach. The sampling technique used the accidental sampling method with a total of 57 respondents. Data was collected using a questionnaire, and data analysis was carried out using the Spearman correlation test using SPSS version 25. The results showed that 96.49% of respondents had a good level of knowledge, while only 3.5% of respondents had awareness of the use of sunscreen, which was a very low percentage. The results of statistical analysis show that there is no significant relationship between the level of knowledge and awareness of the use of sunscreen with a significance value of 0.469 (p > 0.05).